Comoros : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in Comoros during the 1990s. The economic performance of Comoros during 1991-94 was characterized by real growth of about 1.6 percent a year on average, large financial imbalances, an eroding export base, and the accumulation of large domestic and external payments arrears. Public finances came under pressure as revenue performance deteriorated as a result of a narrow tax base, tax exemptions and evasion, and poor tax administration, exacerbated by rising current expenditures, which stemmed in particular from a growing wage bill.